Howell Modified Test for qualitative and quantitative assessment of near phoria - A.V. Kriuchko (Ukrainian Society of Ophthalmologists, 2018)
Introduction. During a routine optometric examination, much attention is paid to a state of accommodation, convergence, and their interaction. Purpose. To improve the Howell test for near phoria with the possibility of qualitative and quantitative assessment of ocular muscle balance for near. Materials and Methods. During a routine optometric examination, 78 patients with mild and moderate myopia were examined for near phoria using the Modified Howell Test (MHT) and the dissociated test with prisms as a control. Results. Mean near heterophoria values were 1.37 ± 0.48 prism diopters by the MHT and 1.39 ± 0.48 prism diopters by the control test with prisms, the difference was insignificant (p<0.05). Normal values of near phoria with complete correction were found in 24.4% of cases. Acceptable values of shifts on either side were found in 30.7% of cases. Exophoria was in 2.6%. Esophoria was found in 42.3% of cases. The absence of differences in examination using the HMT and the control test with prisms was found in 39.8% of cases, taking into account standard deviation of ±1 prism diopters in 68% of cases. Deviation of ±2 prism diopters was found in 23.1%; ±3 and above prism diopters in 8.9%. The means of differences between the tests was 1.03±0.12 prism diopters. Conclusions. The Modified Howell Test can be used for qualitative and quantitative measurements of near phoria during the optometric examination. The phoria tests for near phoria consistently characterize a state of muscular balance of eyes.